Impact of Plyometric and Functional Training on Selected Physical Fitness Parameters among College-Level Volleyball Players - Shahi, Suresh Jang; Sedai, Shyam Prasad (Perspectives on Higher Education, 2025)
Volleyball is one of the most popular sports in Tehrathum District. The research paper aimed to analyze improvements in speed using statistical tests, including the dependent’t’ test, ANCOVA, and Scheffe’s post hoc test. This paper examines the impact of plyometric training with and without functional training on selected physical fitness variables of college Volleyball players in Tehrathum. The paper was conducted among 60 male Volleyball players from different colleges in the district, aged 17 to 24. The participants were randomly assigned to three groups: (1) Plyometric training with functional training (PT+FT), (2) Plyometric training without functional training (PT), and (3) Control group (CG). The 14-week training program was conducted five days per week, with sessions lasting 60 minutes in the morning. The findings indicate a significant improvement in speed in both experimental groups, with the PT+FT group showing the most progress.